One day survey by the Mental Health Act Commission of acute adult psychiatric inpatient wards in England and Wales. Issue 7168 (7th November 1998) - Ford, Richard; Durcan, Graham; Warner, Lesley; Hardy, Pollyanna; Muijen, Matt
Abstract : Abstract: Objectives : To provide (via the Mental Health Act Commission's "national visit") empirical evidence on ward occupancy levels, use of the Mental Health Act 1983, nurse staffing, and care of female patients on acute adult psychiatric wards. Design : One day survey of a stratified random sample. Settings : 119/250 (47%) acute adult psychiatric inpatient units in England and Wales. Subjects : End sample of 263 acute psychiatric inpatient wards. Main outcome measures : Ward occupancy rates; number of patients detained under the Mental Health Act and proportion "absent without leave"; nurse staffing levels, skill mix, and vacancies; proportion of women with self contained, women-only facilities. Results : Mean ward occupancy was 99% (95% confidence interval 97% to 102%). A ward mean of 30% (28% to 32%) of patients were detained under the Mental Health Act; of all detained patients, 1% (1% to 2%) were absent without leave. A ward mean of 0.3 (0.29 to 0.31) nurses were on duty per patient at the time of the visit. An estimated ward mean of 31% (30% to 32%) of nurse staffing may have been through casual contracts higher in inner (48% (43% to 53%)) and outer London (45% (41% to 48%)). On 26% (21% to 32%) of wards, there were no nurses interacting with patients. A ward mean of 36% (30% to 41%) of female patients had self contained, women-only facilities. Conclusions : Attention should focus on improving the quality of acute inpatient psychiatric care as well as of community care.